2012
DOI: 10.1038/nprot.2012.100
|View full text |Cite
|
Sign up to set email alerts
|

Myelination of rodent hippocampal neurons in culture

Abstract: Axons of various hippocampal neurons are myelinated mainly postnatally, which is important for the proper function of neural circuits. Demyelination in the hippocampus has been observed in patients with multiple sclerosis, Alzheimer’s disease or temporal lobe epilepsy. However, very little is known about the mechanisms and exact functions of the interaction between the myelin-making oligodendrocytes and the axons within the hippocampus. This is mainly attributable to the lack of a system suitable for molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…Similarly, dispersed mixed glial cultures established with neurons and oligodendrocytes from cortical tissues 4 or spinal cords 5,6 also contain similar contaminating cell types that are seen with slice cultures and that yield inconsistent amounts of myelin from culture to culture. In contrast, purified neuron-oligodendroglial coculture systems can be established using dorsal root ganglion neurons 7 , retinal ganglion neurons 8 or hippocampal neurons 9,10 . However, preparing these coculture systems involves tedious purification procedures and the maintenance of primary neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, dispersed mixed glial cultures established with neurons and oligodendrocytes from cortical tissues 4 or spinal cords 5,6 also contain similar contaminating cell types that are seen with slice cultures and that yield inconsistent amounts of myelin from culture to culture. In contrast, purified neuron-oligodendroglial coculture systems can be established using dorsal root ganglion neurons 7 , retinal ganglion neurons 8 or hippocampal neurons 9,10 . However, preparing these coculture systems involves tedious purification procedures and the maintenance of primary neurons.…”
Section: Introductionmentioning
confidence: 99%
“…As many neurons are myelinated in the brain, we next examined whether myelination had any effect on the formation of MPS using a previously developed neuron-glia coculture system (31). Myelin sheaths were identified using an antibody against myelin basic protein (MBP).…”
Section: The Mps Structure Is Present In Multiple Specific Subtypes Omentioning
confidence: 99%
“…There is variety evidence showing that cortical and hippocampal neurons reach neurochemical maturation during 14-21 DIV [29][30][31]. On the othr hand, Price et al [26] demonstrated the total number of dendrites and total dendritic length as indices of neuronal maturation in cultured neurons.…”
Section: Effect Of Nlgn1 Knockdown On Maturation Of Primary Cortical mentioning
confidence: 98%